Sexual compatibility of the olive cultivar ‘Kalamata’ assessed by paternity analysis - Seifi, E.; Guerin, J.; Kaiser, B.; Sedgley, M. (Spanish Journal of Agricultural Research, 2012)
Paternity analysis was used to assess the self-incompatibility of the olive (Olea europaea L.) cultivar ‘Kalamata’ and to identify some compatible pollenisers under a Mediterranean-type climate. Eight microsatellite markers were used for genotyping three ‘Kalamata’ mother trees, 120 embryos, and all potential pollen donors. The identified alleles were analysed using FaMoz software and showed that ‘Kalamata’ was highly self-incompatible. Only three ‘Kalamata’ embryos were assigned to ‘Kalamata’ self-fertilisation, even though it was the most available pollen donor. The alleles were also analysed using NTSYS-pc (version 2.02 k) software and identified 54 potential pollen donors in the study site; however, not all of them were located within the effective pollination distance of the mother trees (30 m in olive). According to the results of this study, ‘Kalamata’ (as a host) was compatible with ‘Barnea’, ‘Benito’, and ‘Katsourela’ (six ‘Kalamata’ embryos assigned in each) but incompatible with ‘Arbequina’, ‘Azapa’, and ‘Picual’ (zero ‘Kalamata’ embryos assigned in each). The olive growers could use some of these compatible pollenisers with ‘Kalamata’ to guarantee good fruit set.